2013
DOI: 10.48550/arxiv.1307.1788
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subdivision rules for special cubulated groups

Brian Rushton

Abstract: We find explicit subdivision rules for all special cubulated groups. A subdivision rule for a group produces a sequence of tilings on a sphere which encode all quasi-isometric information for a group. We show how these tilings detect properties such as growth, ends, divergence, etc. We include figures of several worked out examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…In [10], we showed that every compact special cube complex has a fundamental group that is quasi-isometric to the history graph of some subdivision pair.…”
Section: Applicationsmentioning
confidence: 99%
“…In [10], we showed that every compact special cube complex has a fundamental group that is quasi-isometric to the history graph of some subdivision pair.…”
Section: Applicationsmentioning
confidence: 99%